Pyranopyran-1,8-dione, an Active Compound from Vitices Fructus, Attenuates Cigarette-Smoke Induced Lung Inflammation in Mice - Lee, Gihyun (Int J Mol Sci, 2017)
Previously, we isolated and identified pyranopyran-1,8-dione (PPY) from Viticis Fructus, as a bioactive compound possessing anti-inflammatory properties. The present study was aimed to evaluate the preventive benefit of PPY on cigarette–smoke (CS)-induced lung inflammation. C57BL/6 mice were exposed to CS for 2 weeks while PPY was administrated by oral injection 2 h before CS exposure. To validate the anti-inflammatory effects of PPY, the numbers of immune cells in the bronchoalveolar lavage fluid were counted. Proinflammatory cytokines (Tumor necrosis factor-α: TNF-α, IL-6) and keratinocyte chemokine (KC/CXCL1) were also measured. Histopathologic analysis and cellular profiles showed that inflammatory cell infiltrations were significantly decreased in peribronchial and perivascular area by PPY treatment. The alveolar destruction by CS was markedly ameliorated by PPY treatment. In addition, the TNF-α, IL-6, and KC levels were declined in the PPY groups. These observations suggest that PPY has a preventive potential for lung inflammatory diseases.